Phenotypic and Functional Signatures of Peripheral Blood and Spleen Compartments of Cynomolgus Macaques Infected With T. cruzi: Associations With Cardiac Histopathological Characteristics - Sathler-Avelar, Renato; Vitelli-Avelar, Danielle Marquete; Mattoso-Barbosa, Armanda Moreira; Pascoal-Xavier, Marcelo Antônio; Elói-Santos, Silvana Maria; Costa-Rocha, Ismael Artur da; Teixeira-Carvalho, Andréa; Dick, Edward J.; VandeBerg, Jane F.; VandeBerg, John L.; Martins-Filho, Olindo Assis (Frontiers in Cellular and Infection Microbiology, 2021)
We performed a detailed analysis of immunophenotypic features of circulating leukocytes and spleen cells from cynomolgus macaques that had been naturally infected with T. cruzi, identifying their unique and shared characteristics in relation to cardiac histopathological lesion status. T. cruzi-infected macaques were categorized into three groups: asymptomatic [CCC(-)], with mild chronic chagasic cardiopathy [CCC(+)], or with moderate chronic chagasic cardiopathy [CCC(++)]. Our findings demonstrated significant differences in innate and adaptive immunity cells of the peripheral blood and spleen compartments, by comparison with non-infected controls. CCC(+) and CCC(++) hosts exhibited decreased frequencies of monocytes, NK and NKT-cell subsets in both compartments, and increased frequencies of activated CD8+ T-cells and GranA+/GranB+ cells. While a balanced cytokine profile (TNF/IL-10) was observed in peripheral blood of CCC(-) macaques, a predominant pro-inflammatory profile (increased levels of TNFand IFN/IL-10) was observed in both CCC(+) and CCC(++) subgroups. Our data demonstrated that cardiac histopathological features of T. cruzi-infected cynomolgus macaques are associated with perturbations of the immune system similarly to those observed in chagasic humans. These results provide further support for the validity of the cynomolgus macaque model for pre-clinical research on Chagas disease, and provide insights pertaining to the underlying immunological mechanisms involved in the progression of cardiac Chagas disease.